Improving Community Mental Health through Early Detection and Psychological First Aid (PFA) Training for Prospective Mental Health Cadres at Dlingo II Health Center - Ariska, Ike Gustia; Hariyanto, Sheryl Vasya (Faculty of Psychology, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
Mental health is a crucial component of overall well-being, yet it remains an overlooked aspect of community health in Indonesia. This study aimed to improve community mental health by providing training on early detection of mental disorders and Psychological First Aid (PFA) for prospective mental health cadres at the Dlingo II Community Health Center, Bantul Regency, Yogyakarta. Using a quasi-experimental design with a pretest-posttest approach, the intervention involved psychoeducation, practical workshops, and role-play sessions on mental health literacy, early detection using the Self-Reporting Questionnaire (SRQ-20) and SIJIWA application, and basic psychological first aid skills. Data was collected from 29 participants and analyzed using paired sample t-tests. Results showed a significant increase in cadres’ knowledge and skills after the intervention (p < 0.05). Qualitative feedback indicated improved confidence and readiness to support community members experiencing psychological distress. The study concludes that early detection and PFA training can effectively empower community health cadres to play an active role in mental health promotion and prevention. Further integration of structured cadre programs within primary care systems is recommended to enhance sustainability.